Ceramic green body reinforcing agent as well as manufacturing method and application thereof
By mixing the absolutely dry sludge with additives to form a ceramic body reinforcement, the problems of municipal sludge treatment and insufficient strength of ceramic body are solved, and the strength of the tiles is improved and the resource utilization of sludge is achieved, ensuring the ceramic products Safety and environmental protection.
Patent Information
- Application Number
- CN202411256536.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-07
AI Technical Summary
Municipal sludge treatment has problems such as large land occupation, low thermal energy efficiency, and air pollution. The strength of ceramic body reinforcement agent is insufficient when the amount of added is insufficient, which affects granulation when excessive amounts, making it difficult to achieve resource utilization of municipal sludge and dry tiles. Increased intensity.
The ceramic body reinforcement composed of absolute dry sludge, additives and auxiliary agents are used to obtain absolute dry sludge, water-washed sludge and calcined kaolin soil obtained by decomposing impurities, combining water release, deodorization and sterilization, flocculation and dehydration drying treatment. The additives are mixed to form a ceramic body reinforcement, and 0.05% to 0.5% by weight is added to the preparation of ceramic tile to enhance the strength of the dry blank.
The resource utilization of municipal sludge has been achieved, the strength of the dry blank of ceramic tile has been significantly improved by more than 20%, and the dehydration and settlement effect have been improved through the optimization of flocculant, ensuring the safety and environmental friendliness of ceramic products.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sludge treatment, and in particular to a ceramic body reinforcing agent and a manufacturing method and application thereof. Background Art
[0002] As relevant national departments gradually pay more attention to the management of solid waste and environmental protection standards are gradually improved, the treatment of municipal sludge has become a very urgent issue. Municipal sludge is a solid waste with high water content, high organic matter content and a large amount of bacteria, viruses, insect eggs, heavy metals and other impurities generated in the process of municipal sewage treatment. In the process of domestic municipal sewage treatment, municipal sludge is treated by traditional landfill and incineration methods, which have the problems of occupying large land space, low thermal efficiency, and air pollution. In order to reduce the adverse effects of municipal sludge on the environment, it is necessary to reduce the amount of municipal sludge, make it harmless, and treat it as a resource.
[0003] Ceramic body reinforcing agents generally use high molecular weight organic substances such as methyl cellulose, sodium polyacrylate, starch polymers, benzene polyesters, amides, etc. However, most ceramic body reinforcing agents have the problem that when the addition amount is small, the body strength is insufficient, resulting in a high breakage rate; when the addition amount is large, the slurry thickens and affects the granulation, which is not conducive to its application in ceramic production. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a ceramic body reinforcing agent, which can realize the resource utilization of municipal sludge, and the ceramic body reinforcing agent can significantly improve the dry body strength of ceramic tiles with a relatively small addition amount.
[0005] Another technical problem to be solved by the present invention is to provide a method for preparing a ceramic body reinforcing agent, which is simple in preparation and high in efficiency.
[0006] The technical problem that the present invention needs to solve is to provide an application of a ceramic body reinforcing agent to obtain a ceramic tile with high dry body strength.
[0007] In order to solve the above problems, the present invention discloses a ceramic body reinforcing agent, comprising the following components in parts by weight: 50-70 parts of absolute dry sludge, 25-50 parts of additives, and 0.5-10 parts of auxiliary agents; the total weight of each component is 100 parts;
[0008] The absolutely dry sludge is obtained by removing impurities, releasing bound water, deodorizing and sterilizing, flocculating, and dehydrating and drying municipal sludge.
[0009] As an improvement of the above technical solution, the absolute dry sludge includes the following components in weight percentage: 8% to 12% aluminum oxide, 20% to 25% silicon dioxide, 4% to 8% iron oxide, 0.1% to 1% titanium dioxide, 0.5% to 3% calcium oxide, 0.5% to 1% magnesium oxide, 1% to 2% potassium oxide, 0.5% to 2% sodium oxide, and 45% to 55% loss on ignition.
[0010] As an improvement of the above technical solution, the additive is one or more of washed ball clay, washed kaolin, calcined kaolin, quartz sand, and bentonite.
[0011] As an improvement of the above technical solution, the washed ball clay comprises the following components in weight percentage: 28% to 33% aluminum oxide, 50% to 55% silicon dioxide, 0.1% to 1.5% iron oxide, 0.01% to 0.5% titanium dioxide, 0.01% to 0.5% calcium oxide, 0.01% to 0.5% magnesium oxide, 0.1% to 2% potassium oxide, 0.1% to 1% sodium oxide, and 5% to 15% loss on ignition;
[0012] The washed kaolin comprises the following components in weight percentage: 35% to 42% aluminum oxide, 45% to 55% silicon dioxide, 0.01% to 1% iron oxide, 0.01% to 1% titanium dioxide, 0.01% to 0.5% calcium oxide, 0.01% to 0.5% magnesium oxide, 0.1% to 1% potassium oxide, 0.1% to 1% sodium oxide, and 5% to 15% loss on ignition;
[0013] The calcined kaolin comprises the following components in weight percentage: 45% to 50% aluminum oxide, 45% to 50% silicon dioxide, 0.01% to 1% iron oxide, 0.01% to 1% titanium dioxide, 0.01% to 0.5% calcium oxide, 0.01% to 0.5% magnesium oxide, 0.1% to 1% potassium oxide, 0.1% to 1% sodium oxide, and 0.5% to 5% loss on ignition;
[0014] The quartz sand comprises the following components in weight percentage: 1% to 8% aluminum oxide, 90% to 98% silicon dioxide, 0.1% to 1% iron oxide, 0.01% to 1% titanium dioxide, 0.01% to 0.5% calcium oxide, 0.01% to 1% magnesium oxide, 0.1% to 3% potassium oxide, 0.1% to 1% sodium oxide, and 0.5% to 5% loss on ignition;
[0015] The bentonite comprises the following components in weight percentage: 15% to 20% aluminum oxide, 70% to 75% silicon dioxide, 0.1% to 2% iron oxide, 0.01% to 1% titanium dioxide, 0.01% to 0.5% calcium oxide, 0.01% to 1% magnesium oxide, 0.1% to 3% potassium oxide, 0.1% to 1% sodium oxide, and 5% to 10% loss on ignition.
[0016] As an improvement of the above technical solution, the auxiliary agent is one or more of sodium tripolyphosphate, sodium hexapolyphosphate, and sodium metasilicate pentahydrate.
[0017] Correspondingly, the present invention also discloses a method for manufacturing a ceramic body reinforcing agent, comprising the following steps:
[0018] (1) Crushing the absolutely dry sludge;
[0019] (2) crushing the additives;
[0020] (3) The absolutely dry sludge, additives and auxiliary agents are mixed uniformly according to a certain proportion to obtain the ceramic body reinforcing agent.
[0021] As an improvement of the above technical solution, the absolutely dry sludge is obtained by processing in the following steps:
[0022] (1.1) Put the municipal sludge into the pulping tank and add water to make the slurry until the water content of the sludge is 90% to 98%;
[0023] (1.2) removing particles with larger particle sizes from the mud and grinding the mud after impurities removal;
[0024] (1.3) The ground slurry is sent to a reaction tank, chlorate is first added, then one or more of sulfur-containing compounds, chlorine-containing compounds, and polychloride are added, and finally alkali is used to neutralize the slurry;
[0025] (1.4) Adding flocculants to the sludge to aggregate the sludge particles in the sludge;
[0026] (1.5) Dewatering the settled sludge until the moisture content of the sludge is 30% to 50%;
[0027] (1.6) The dehydrated sludge is dried to obtain absolutely dry sludge.
[0028] As an improvement of the above technical solution, the flocculant comprises the following raw materials in weight percentage: 6% to 20% polyacrylamide, 40% to 60% starch, 20% to 40% maltodextrin, and 1% to 10% functional additive;
[0029] The dosage of the flocculant is 2wt% to 4wt%.
[0030] As an improvement of the above technical solution, the drying process includes:
[0031] Performing microwave drying treatment, wherein the microwave frequency of the microwave drying treatment is 2000MHz to 2450MHz, and the microwave power is 320W to 640W;
[0032] Alternatively, a low temperature drying treatment is performed, wherein the temperature of the low temperature drying treatment is 60°C to 80°C.
[0033] Correspondingly, the present invention also discloses the use of the above-mentioned ceramic body reinforcing agent in the preparation of ceramic tiles, wherein the addition amount of the ceramic body reinforcing agent is 0.05wt% to 0.5wt% of the ceramic body dry material.
[0034] The implementation of the present invention has the following beneficial effects:
[0035] 1. The present invention mixes the absolutely dry sludge obtained from municipal sludge treatment with additives and auxiliary agents to obtain a ceramic body reinforcing agent. The molecular chains of components such as organic matter, sodium humate, and flocculants added during the flocculation process in the sludge have a network structure, which can be bonded to the body components to improve the strength of the tile; in addition, during the firing process of the tile, the heavy metals in the absolutely dry sludge are converted into stable compounds and solidified in the tile, which will not cause harm to the environment and human body. The ceramic body reinforcing agent of the present invention is added at 0.05wt% to 0.5wt% of the dry material of the ceramic body, and the dry body strength of the obtained tile can be increased by more than 20%.
[0036] 2. The present invention adds chlorate during the municipal sludge treatment process to release internal bound water and improve the dewatering performance of the sludge; the addition of sulfur-containing compounds, chlorine-containing compounds or polychlorides can remove bacteria, viruses, insect eggs, etc. in the municipal sludge, ensuring the safety of the ceramics prepared subsequently; the flocculant is optimized to facilitate the adsorption and bridging of the flocculant, thereby improving the sludge dewatering performance and the sedimentation effect on substances such as heavy metals. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in further detail below.
[0038] The present invention provides a ceramic body reinforcing agent, comprising the following components in parts by weight: 50-70 parts of absolute dry sludge, 25-50 parts of additives, and 0.5-10 parts of auxiliary agents; the total mass of each component is 100 parts. The absolute dry sludge is obtained by removing impurities, releasing bound water, deodorizing and sterilizing, flocculating, and dehydrating municipal sludge.
[0039] Specifically, the absolutely dry sludge includes the following components in weight percentage: 8% to 12% aluminum oxide, 20% to 25% silicon dioxide, 4% to 8% iron oxide, 0.1% to 1% titanium dioxide, 0.5% to 3% calcium oxide, 0.5% to 1% magnesium oxide, 1% to 2% potassium oxide, 0.5% to 2% sodium oxide, and 45% to 55% loss on ignition.
[0040] Among them, aluminum oxide can improve the chemical stability of dried sludge, silicon dioxide can improve the weather resistance of dried sludge, and iron oxide, calcium oxide, magnesium oxide, potassium oxide, and sodium oxide as flux materials can appropriately reduce the firing temperature of the green body during high-temperature firing.
[0041] After being processed, the municipal sludge of the present invention removes substances such as bacteria, viruses, and insect eggs that are detrimental to human health. The molecular chains of components such as organic matter, sodium humate, and flocculants added during the flocculation process in the municipal sludge have a network structure and can be bonded together with the green body components to improve the strength of the tiles. In addition, during the firing process of the tiles, the heavy metals in the sludge are converted into stable compounds and solidified in the tiles, which will not cause harm to the environment and the human body.
[0042] The additive is one or more of washed ball clay, washed kaolin, calcined kaolin, quartz sand and bentonite. The additive is used to adjust the effect of the ceramic body reinforcing agent on the ceramic whiteness and firing effect. The preferred additive of the present invention is used, and the additive reacts with the absolutely dry sludge to improve the stability of the absolutely dry sludge.
[0043] Specifically, the washed ball clay comprises the following components in weight percentage: 28% to 33% aluminum oxide, 50% to 55% silicon dioxide, 0.1% to 1.5% iron oxide, 0.01% to 0.5% titanium dioxide, 0.01% to 0.5% calcium oxide, 0.01% to 0.5% magnesium oxide, 0.1% to 2% potassium oxide, 0.1% to 1% sodium oxide, and 5% to 15% loss on ignition.
[0044] The washed kaolin comprises the following components in weight percentage: 35% to 42% aluminum oxide, 45% to 55% silicon dioxide, 0.01% to 1% iron oxide, 0.01% to 1% titanium dioxide, 0.01% to 0.5% calcium oxide, 0.01% to 0.5% magnesium oxide, 0.1% to 1% potassium oxide, 0.1% to 1% sodium oxide, and 5% to 15% loss on ignition.
[0045] The calcined kaolin comprises the following components in weight percentage: 45% to 50% aluminum oxide, 45% to 50% silicon dioxide, 0.01% to 1% iron oxide, 0.01% to 1% titanium dioxide, 0.01% to 0.5% calcium oxide, 0.01% to 0.5% magnesium oxide, 0.1% to 1% potassium oxide, 0.1% to 1% sodium oxide, and 0.5% to 5% loss on ignition.
[0046] The quartz sand comprises the following components in weight percentage: 1% to 8% aluminum oxide, 90% to 98% silicon dioxide, 0.1% to 1% iron oxide, 0.01% to 1% titanium dioxide, 0.01% to 0.5% calcium oxide, 0.01% to 1% magnesium oxide, 0.1% to 3% potassium oxide, 0.1% to 1% sodium oxide, and 0.5% to 5% loss on ignition.
[0047] The bentonite comprises the following components in weight percentage: 15% to 20% aluminum oxide, 70% to 75% silicon dioxide, 0.1% to 2% iron oxide, 0.01% to 1% titanium dioxide, 0.01% to 0.5% calcium oxide, 0.01% to 1% magnesium oxide, 0.1% to 3% potassium oxide, 0.1% to 1% sodium oxide, and 5% to 10% loss on ignition.
[0048] Among them, aluminum oxide can improve the chemical stability of the additive, silicon dioxide can improve the weather resistance of the additive, and iron oxide, calcium oxide, magnesium oxide, potassium oxide, and sodium oxide as flux materials can appropriately reduce the firing temperature of the green body during high-temperature firing.
[0049] The auxiliary agent is one or more of sodium tripolyphosphate, sodium hexapolyphosphate, and sodium metasilicate pentahydrate. The auxiliary agent is used to adjust the effect of the ceramic body reinforcing agent on the performance of the ceramic slurry. The preferred auxiliary agent of the present invention is used to improve the overall fluidity of the slurry and the formability of the ceramic body after the ceramic reinforcing agent is added.
[0050] The present invention also provides a method for manufacturing a ceramic body reinforcing agent, comprising the following steps:
[0051] (1) Crush the absolutely dry sludge.
[0052] The absolutely dry sludge is crushed to improve its uniformity of dispersion in the ceramic blank dry material. Specifically, the absolutely dry sludge is crushed to less than 80 meshes, preferably, the absolutely dry sludge is crushed to 80-120 meshes. If it is less than 120 meshes, its dispersion performance is not significantly improved, and the complexity of the preparation process is increased; if it is greater than 80 meshes, it is not conducive to its uniformity of dispersion.
[0053] The absolutely dry sludge is obtained by processing in the following steps:
[0054] (1.1) Put the municipal sludge into the pulping tank and add water to make the slurry until the water content of the sludge is 90% to 98%.
[0055] (1.2) Remove the larger particles from the mud, and grind and break the mud after impurities are removed.
[0056] (1.3) The ground mud is sent to the reaction tank, where chlorate is first added, followed by sulfur compounds, chlorine compounds or polychlorides, and finally alkali is used to neutralize the mud.
[0057] Chlorate can release internal bound water and improve the dehydration performance of sludge. Specifically, chlorate can be sodium hypochlorite or potassium hypochlorite, but it is not limited to this. The addition of sulfur-containing compounds, chlorine-containing compounds or polychlorides can remove bacteria, viruses, insect eggs, etc. in municipal sludge, play a role in sterilization and deodorization, and ensure the safety of subsequent ceramics. Specifically, the sulfur-containing compound can be ferrous sulfate, the chlorine-containing compound can be ferrous chloride or aluminum chloride, and the polychloride can be polyferric chloride or polyaluminum chloride, but it is not limited to this. After deodorization and sterilization, the sludge is acidic as a whole, which is not conducive to the subsequent production of ceramics. Therefore, it is necessary to adjust the pH of the sludge. In one embodiment, a weak base is used to neutralize the mud. Specifically, the weak base can be quicklime, sodium carbonate or sodium bicarbonate, but it is not limited to this.
[0058] (1.4) Add flocculants into the sludge to aggregate the sludge particles in the sludge.
[0059] The flocculant can be an inorganic flocculant such as aluminum sulfate, ferric chloride, or an organic flocculant such as polyacrylamide.
[0060] In one embodiment, the flocculant comprises the following raw materials in weight percentage: 6% to 20% polyacrylamide, 40% to 60% starch, 20% to 40% maltodextrin, and 1% to 10% functional additives, which include but are not limited to initiators, catalysts, and linkers.
[0061] The preparation method of the flocculant comprises: mixing modified starch and maltodextrin, adding polyacrylamide and functional additives in sequence and mixing, stirring at 20° C. to 40° C., filtering, drying and grinding to obtain the flocculant.
[0062] The dosage of the flocculant is 2wt% to 4wt%.
[0063] Compared with traditional polyacrylamide flocculants, the flocculant of the present invention grafts starch and polyacrylamide for copolymerization, and the adsorption bridging of the flocculant can accelerate the deposition, thereby improving the dehydration and the sedimentation effect of heavy metals and other substances, further improving the performance of the prepared ceramic body reinforcing agent, and only 2wt% to 4wt% of the addition amount is required to achieve efficient flocculation of sludge.
[0064] (1.5) Dehydrate the settled sludge until the moisture content of the sludge is 30% to 50%.
[0065] (1.6) The dehydrated sludge is dried to obtain absolutely dry sludge.
[0066] The drying treatment may be microwave drying treatment, wherein the microwave frequency of the microwave drying treatment is 2000 MHz to 2450 MHz, and the microwave power is 320 W to 640 W.
[0067] The drying treatment may be low-temperature drying treatment, with the treatment temperature being 60°C to 80°C.
[0068] (2) Crush the additives.
[0069] Specifically, the additive is crushed to less than 80 meshes, preferably, the additive is crushed to 80-120 meshes.
[0070] (3) The absolutely dry sludge, additives and auxiliary agents are mixed uniformly according to a certain proportion to obtain the ceramic body reinforcing agent.
[0071] Municipal sludge is relatively loose as a whole, has small particles after flocculation, and has unstable dehydration performance. Therefore, the present invention can obtain absolutely dry sludge with a moisture content of 30% to 50% by removing impurities, removing bound water, deodorizing and sterilizing, settling, and dehydrating and drying municipal sludge.
[0072] The present invention also provides an application of a ceramic body reinforcing agent in the preparation of ceramic tiles. During the preparation of ceramic tiles, the ceramic body reinforcing agent of the present invention is added at 0.05wt% to 0.5wt% of the ceramic body dry material, which can increase the strength of the ceramic body dry material by 20% to 45%.
[0073] The present invention will be further described below with specific embodiments:
[0074] Example 1
[0075] The present embodiment provides a ceramic body reinforcing agent, comprising the following components in parts by weight: 70 parts of absolute dry sludge, 25 parts of washed ball clay, and 5 parts of sodium hexapolyphosphate.
[0076] The absolutely dry sludge includes the following components in weight percentage: 8% aluminum oxide, 25% silicon dioxide, 6% iron oxide, 0.8% titanium dioxide, 2% calcium oxide, 0.8% magnesium oxide, 1.3% potassium oxide, 1.1% sodium oxide, and ignition loss of 55%.
[0077] The washed ball clay includes the following components in weight percentage: 30% aluminum oxide, 55% silicon dioxide, 1% iron oxide, 0.2% titanium dioxide, 0.2% calcium oxide, 0.2% magnesium oxide, 1.5% potassium oxide, 0.6% sodium oxide, and 11.3% loss on ignition.
[0078] Accordingly, the method for manufacturing the ceramic body reinforcing agent comprises the following steps:
[0079] (1) Crush the absolutely dry sludge to 100 mesh.
[0080] (1.1) Put the municipal sludge into the pulping tank and add water to make the sludge slurry until the water content of the sludge is 95%;
[0081] (1.2) removing particles with larger particle sizes from the mud and grinding the mud after impurities removal;
[0082] (1.3) The ground mud is sent to the reaction tank, sodium hypochlorite is added first, then ferrous sulfate is added, and finally quicklime is used to neutralize the mud;
[0083] (1.4) Add FeCl to the slurry 3 Flocculants aggregate the sludge particles in the slurry, FeCl 3 The dosage of flocculant is 6wt%;
[0084] (1.5) Dewater the settled sludge until the moisture content of the sludge is 35%;
[0085] (1.6) The dehydrated sludge is subjected to low-temperature drying treatment at 70°C to obtain absolutely dry sludge.
[0086] (2) Crush the additives to 100 mesh.
[0087] (3) The absolutely dry sludge, additives and auxiliary agents are mixed uniformly according to a certain proportion to obtain the ceramic body reinforcing agent.
[0088] Example 2
[0089] This embodiment provides a ceramic body reinforcing agent, comprising the following components in parts by weight: 50 parts of absolute dry sludge, 46 parts of bentonite, and 4 parts of sodium metasilicate pentahydrate.
[0090] The absolutely dry sludge includes the following components in weight percentage: 12% aluminum oxide, 20% silicon dioxide, 7.8% iron oxide, 0.6% titanium dioxide, 2.5% calcium oxide, 0.6% magnesium oxide, 1% potassium oxide, 0.5% sodium oxide, and 55% loss on ignition.
[0091] The bentonite includes the following components in weight percentage: 18% aluminum oxide, 72% silicon dioxide, 0.3% iron oxide, 0.2% titanium dioxide, 0.08% calcium oxide, 0.05% magnesium oxide, 2% potassium oxide, 0.6% sodium oxide, and ignition loss of 6.77%.
[0092] In the preparation method, the dehydrated sludge is subjected to microwave drying treatment at a microwave frequency of 2450 MHz and a microwave power of 400 W to obtain absolutely dry sludge.
[0093] The rest are the same as in Example 1.
[0094] Example 3
[0095] This embodiment provides a ceramic body reinforcing agent, comprising the following components in parts by weight: 65 parts of absolute dry sludge, 30 parts of calcined kaolin, and 5 parts of sodium metasilicate pentahydrate.
[0096] The absolutely dry sludge includes the following components in weight percentage: 10% aluminum oxide, 23% silicon dioxide, 6% iron oxide, 0.8% titanium dioxide, 2.3% calcium oxide, 0.6% magnesium oxide, 1.5% potassium oxide, 1.2% sodium oxide, and 54.6% loss on ignition.
[0097] The calcined kaolin includes the following components in weight percentage: 48% aluminum oxide, 47% silicon dioxide, 0.06% iron oxide, 0.04% titanium dioxide, 0.03% calcium oxide, 0.04% magnesium oxide, 0.2% potassium oxide, 0.3% sodium oxide, and ignition loss of 4.33%.
[0098] In the preparation method, the flocculant comprises the following raw materials in weight percentage: 15% polyacrylamide, 50% starch, 25% maltodextrin, and 10% functional additive. The dosage of the flocculant is 3wt%.
[0099] The rest are the same as in Example 1.
[0100] The ceramic green body reinforcing agents prepared in Examples 1 to 3 were added to the ceramic green body dry material in proportion, and the slurry fluidity was tested using a viscometer. The ceramic tile pressing method was used for pressing and testing. The specific results are as follows:
[0101]
[0102] It can be seen from the data in the table that the ceramic body reinforcer provided by the present invention can significantly improve the dry body strength of the tile without affecting the fluidity of the slurry. The ceramic reinforcer can be well dispersed in the dry ceramic body, and a small amount of ceramic reinforcer can improve the dry body strength of the tile.
[0103] The above is a preferred embodiment of the invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the invention. These improvements and modifications are also considered to be within the scope of protection of the invention.
Claims
1. A ceramic body reinforcing agent, characterized in that: The invention comprises the following components in parts by weight: 50 to 70 parts of absolute dry sludge, 25 to 50 parts of additives, and 0.5 to 10 parts of auxiliary agents; the total weight of each component is 100 parts; The absolutely dry sludge is obtained by removing impurities, releasing bound water, deodorizing and sterilizing, flocculating, and dehydrating and drying municipal sludge.
2. The ceramic body reinforcing agent according to claim 1, characterized in that The absolutely dry sludge comprises the following components in weight percentage: 8% to 12% aluminum oxide, 20% to 25% silicon dioxide, 4% to 8% iron oxide, 0.1% to 1% titanium dioxide, 0.5% to 3% calcium oxide, 0.5% to 1% magnesium oxide, 1% to 2% potassium oxide, 0.5% to 2% sodium oxide, and 45% to 55% loss on ignition.
3. The ceramic body reinforcing agent according to claim 1, characterized in that The additive is one or more of washed ball clay, washed kaolin, calcined kaolin, quartz sand and bentonite.
4. The ceramic body reinforcing agent according to claim 3, characterized in that The washed ball clay comprises the following components in weight percentage: 28% to 33% aluminum oxide, 50% to 55% silicon dioxide, 0.1% to 1.5% iron oxide, 0.01% to 0.5% titanium dioxide, 0.01% to 0.5% calcium oxide, 0.01% to 0.5% magnesium oxide, 0.1% to 2% potassium oxide, 0.1% to 1% sodium oxide, and 5% to 15% loss on ignition; The washed kaolin comprises the following components in weight percentage: 35% to 42% aluminum oxide, 45% to 55% silicon dioxide, 0.01% to 1% iron oxide, 0.01% to 1% titanium dioxide, 0.01% to 0.5% calcium oxide, 0.01% to 0.5% magnesium oxide, 0.1% to 1% potassium oxide, 0.1% to 1% sodium oxide, and 5% to 15% loss on ignition; The calcined kaolin comprises the following components in weight percentage: 45% to 50% aluminum oxide, 45% to 50% silicon dioxide, 0.01% to 1% iron oxide, 0.01% to 1% titanium dioxide, 0.01% to 0.5% calcium oxide, 0.01% to 0.5% magnesium oxide, 0.1% to 1% potassium oxide, 0.1% to 1% sodium oxide, and 0.5% to 5% loss on ignition; The quartz sand comprises the following components in weight percentage: 1% to 8% aluminum oxide, 90% to 98% silicon dioxide, 0.1% to 1% iron oxide, 0.01% to 1% titanium dioxide, 0.01% to 0.5% calcium oxide, 0.01% to 1% magnesium oxide, 0.1% to 3% potassium oxide, 0.1% to 1% sodium oxide, and 0.5% to 5% loss on ignition; The bentonite comprises the following components in weight percentage: 15% to 20% aluminum oxide, 70% to 75% silicon dioxide, 0.1% to 2% iron oxide, 0.01% to 1% titanium dioxide, 0.01% to 0.5% calcium oxide, 0.01% to 1% magnesium oxide, 0.1% to 3% potassium oxide, 0.1% to 1% sodium oxide, and 5% to 10% loss on ignition.
5. The ceramic body reinforcing agent according to claim 1, characterized in that: The auxiliary agent is one or more of sodium tripolyphosphate, sodium hexapolyphosphate and sodium metasilicate pentahydrate.
6. A method for producing a ceramic body reinforcing agent according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Crushing the absolutely dry sludge; (2) crushing the additives; (3) The absolutely dry sludge, additives and auxiliary agents are mixed uniformly according to a certain proportion to obtain the ceramic body reinforcing agent.
7. The method for producing a ceramic body reinforcing agent according to claim 6, characterized in that: The absolutely dry sludge is obtained by processing in the following steps: (1.1) Put the municipal sludge into the pulping tank and add water to make the slurry until the water content of the sludge is 90% to 98%; (1.2) removing particles with larger particle sizes from the mud and grinding the mud after impurities removal; (1.3) The ground slurry is sent to a reaction tank, chlorate is first added, then one or more of sulfur-containing compounds, chlorine-containing compounds, and polychloride are added, and finally alkali is used to neutralize the slurry; (1.4) Adding flocculants to the sludge to aggregate the sludge particles in the sludge; (1.5) Dewatering the settled sludge until the moisture content of the sludge is 30% to 50%; (1.6) The dehydrated sludge is dried to obtain absolutely dry sludge.
8. The method for producing a ceramic body reinforcing agent according to claim 6, characterized in that: The flocculant comprises the following raw materials in weight percentage: 6% to 20% polyacrylamide, 40% to 60% starch, 20% to 40% maltodextrin, and 1% to 10% functional additives; The dosage of the flocculant is 2wt% to 4wt%.
9. The method for producing a ceramic body reinforcing agent according to claim 6, characterized in that: The drying process comprises: Performing microwave drying treatment, wherein the microwave frequency of the microwave drying treatment is 2000MHz to 2450MHz, and the microwave power is 320W to 640W; Alternatively, a low temperature drying treatment is performed, wherein the temperature of the low temperature drying treatment is 60°C to 80°C.
10. Use of the ceramic body reinforcing agent according to any one of claims 1 to 5 in the preparation of ceramic tiles, characterized in that: The amount of the ceramic green body reinforcing agent added is 0.05wt% to 0.5wt% of the ceramic green body dry material.
Citation Information
Patent Citations
Ceramic green body reinforcing agent and application thereof
CN102584253A
Ceramic body reinforcing agent and application thereof
CN103420680A
Novel sludge brick making technique
CN104649650A
Recycling method of reclaimed material and ceramic tile
CN115893982A
Improvements in the manufacture of pottery or the like
GB253184A